2018
DOI: 10.1016/j.ijvsm.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofMonodora myristicaextracts on crude petroleum oil-contaminated catfish (Clarias gariepinus) diet in rats

Abstract: Humans and animals are constantly exposed to crude petroleum contaminated diets in petroleum producing areas of the world. As a result, researches are on-going to find simple ameliorative agent against crude petroleum contaminated diet toxicity. The aim of this study was to evaluate the protective effect of Monodora myristica on some biochemical parameters of rats fed with crude petroleum oil contaminated catfish diet (CPO-CCD). Thirty male albino rats were separated into six groups of five rats as follows: gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…These showed that the C. odorata leaves extracts may help in the prevention of liver tissue damage. Similar protections by plant extracts were documented [44,51,52] Serum and kidney concentrations of urea and creatinine are indices of renal function. Consequent rise in urea and creatinine serum levels are pointers to impaired renal function [53].…”
Section: Resultssupporting
confidence: 68%
“…These showed that the C. odorata leaves extracts may help in the prevention of liver tissue damage. Similar protections by plant extracts were documented [44,51,52] Serum and kidney concentrations of urea and creatinine are indices of renal function. Consequent rise in urea and creatinine serum levels are pointers to impaired renal function [53].…”
Section: Resultssupporting
confidence: 68%
“…This assertion is not surprising since earlier studies indicated that petroleum stimulated damages are preceded by the formation of free radicals that culminates in macromolecu-lar damage [44,45]. Therefore, the potency of petroleum and related chemicals are arrested in the presence of a sufficient amount of antioxidants [9,46,47]. The efficacy of JFME against DNA damage may be predicated on the rich bioactive compounds in Acanthaceae family, of which Justicia flava is a member [48].…”
Section: Resultsmentioning
confidence: 99%
“…The filtrate was evaporated to dryness using a water bath which produced a yield of 13.91 g/100 g of ground leaves. The extract was stored at -8 • C until required [9].…”
Section: Preparation Of Plant Extractmentioning
confidence: 99%
See 2 more Smart Citations